Nutritional and antioxidant profiles of blackberry and raspberry genotypes - Mostafa Farajpour; Seyed Rasoul Ziatabar Ahmadi; Malihe Talebi Aouei; Mahmoud Reza Ramezanpour; Mohammad Sadat-Hosseini; Shokrollah Hajivand (BMC Plant Biology)
Abstract Background Blackberries and raspberries are nutritionally rich fruits, yet comprehensive studies assessing both mineral composition and antioxidant activity across diverse genotypes—particularly in Iran—remain limited. This study addresses this gap as the first to systematically evaluate twelve raspberry and blackberry cultivars cultivated in northern Iran, providing novel insights into genotype-specific variations in micronutrients (K, P, Ca, Mg, Fe, Mn, Cu) and antioxidant profiles (DPPH, FRAP). Results Distinct genotypic groupings emerged via cluster analysis, with blackberries (TripleCrown, French, Reuben) and raspberries (e.g., Saanich, KiwiGold) forming separate clusters. Principal component analysis (PCA) revealed three components explaining 77% of variance, highlighting strong correlations between genotype, minerals, and antioxidants. Potassium dominated mineral content (0.73–1.21%), with raspberry ‘Summit’ (1.21%) and ‘KiwiGold’ (1.08%) as top performers. Remarkably, the raspberry cultivar ‘Saanich’ demonstrated exceptional levels of iron (159.5 ppm) and manganese (10.5 ppm), surpassing those of other cultivars. Blackberries surpassed raspberries in antioxidant activity: DPPH values ranged from 184.43 µg/ml (‘TripleCrown’) to 316.02 µg/ml (‘Encore’), while FRAP results showed blackberry ‘TripleCrown’ (17.28 mg Fe²⁺/g DW) outperforming raspberries by 36–57%. Conclusion This research highlights the potential of selected cultivars to enhance dietary intake of essential minerals, supporting both consumer health and breeding efforts aimed at improving nutritional quality in berry cultivars.